THE EFFECT OF FIRM SIZE, PROFITABILITY, AND LEVERAGE ON EXECUTIVE COMPENSATION: A STUDY OF BANKING SECTOR IN INDONESIA STOCK EXCHANGE (IDX) - Anggraini, Laila B1034161010 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
ABSTRACKThis study aims to define the factors that affect the amount of executive compensation at companies such as ROA, size, and DAR in banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 with the agency theory approach. This research uses a quantitative approach using multiple linear regression methods to analyze the data. The samples in this study are a banking company listed on the Indonesia Stock Exchange (IDX) in 2018 which is equal to 40 companies. The findings of this study are that size and ROA have a significant positive effect on executive compensation. Meanwhile, DER has no significant effect on executive compensation.The result of the study showed that from the three independent variables, two of them have a significant positive effect, meanwhile the other independent variable has no significant effect. Firm size and Return On Asset (ROA) have a significant positive effect on Executive Compensation at the 5% level of significance. Debt to Asset Ratio (DAR) has no significant effect on Executive Compensation.Keywords: Executive Compensation, Agency Theory, Company Size, Profitability, LeverageÂ Aduda, J. (2011). The Relationshop Between Excutive Compensation and Firm Performance in The Kenyan Banking Sector. Jurnal Accounting and Taxation, 3 (6), 130-139.Akdon, & Riduwan. (2008). Rumus dan Data dalam Aplikasi Penelitian. Bandung: Afabeta.Anthony, & Govindarajan. (2005). Management Control System (Edisi 11 ed.). Jakarta: Salemba.Arikunto, S. (2013). Prosedur Penelitian : Suatu Pendekatan Praktek. Jakarta: PT. Rineka Cipta.Bank Indonesia. (1998). UU No.10 Tahun 1998. Tentang Perubahan Terhadap UU No. 7 tahun 1992. Jakarta.Burchman, S., & Jones, B. (2006). Executive Compensation as a Support for a Growth Strategy. WORLDATWORK JOURNAL, 15 (3), 39-46.Darmadi, S. (2011). Board compensation, corporate governance, and firm peformance in Indonesia. Forthcoming in the journal Corporate Ownership and Control. Dipetik November 8, 2019, dari http://ssrn.comDestriana, N. (2015). Masalah dan Biaya Keagenan. Jurnal Bisnis dan Akuntansi, 17 (2), 125-133.Ghozali, I. (2005). Aplikasi Analisis Multivariate dengan SPSS.Ghozali, I. (2011). Aplikasi Analisis Multivariate Dengan Program IBM SPSS.Ghozali, R. A., & Fuad. (2015). Pengaruh Struktur Kepemilikan, Kinerja dan Risiko terhadap Kompensasi Eksekutif. Diponegoro of Journal Accounting, 4 (2), 1-10.Harahap, S. S. (2004). Analisis Kritis Atas Laporan Keuangan. Jakarta: PT. Raja Grafindo Persada.Hery. (2016). Analisis Laporan Keuangan Integrated and Comprehensive Edition. Jakarta: PT. Garuda Widiasrana Indonesia.Indonesia, I. A. (2015). Standar Akuntansi Keuangan. Diambil kembali dari PSAK 1 Penyajian Laporan Keuangan: http://iaiglobal.or.id/v03/standar-akuntansi-keuangan/pernyataan-sak-7-psak-1-penyajian-laporan-keuanganIqbal, J., & Shehzad, S. (2010). Relationship of Cost of Governance and Firm's Profitability in Pakistan. Dipetik November 8, 2019, dari http://ssrn.comIskandar, A. F., & Suardana, K. A. (2016). Pengaruh Ukuran Perusahaan, Return On Asset Dan Winner/Loser Stock Terhadap Prakrik Perataan Laba. E-Jurnal Akuntansi Universitas Udayana, 14 (2), 805-834.Kasmir. (2012). Analisis Laporan Keuangan. Jakarta: PT. Raja Grafindo Persada.Kasmir. (2013). Analisis Laporan Keuangan. Jakarta: PT Raja Grafindo Persada.Krisherti, A. (2016). Pengaruh Struktur Kepemilikan, Risiko Litigasi Dan Leverage Terhadap Kompensasi Eksekutif. STIE Perbanas Surabaya.Kristanto, J. C. (2018). KINERJA PERUSAHAAN TERHADAP KOMPENSASI EKSEKUTIF PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ 45 PERIODE 2012-2016. Calyptra: Jurnal Ilmiah Mahasiswa Universitas Surabaya, 7(1), 1627 - 1641.Mardiyati, U., Devi, M. S., & Suherman. (2013). Pengaruh Kinerja Perusahaan, Corporate Governance dan Shareholder Payout terhadap Kompensasi Eksekutif. Jurnal Riset Manajemen Sains Indonesia(JRMSI), 4 (2), 167-183.Muhammad, D. (2011, January 21). Republika.co.id. Dipetik November 2019, 7, dari Ekonomi: https://m.republika.co.id/berita/breaking-news/ekonomi/11/01/23/160123-gaji-bankir-tinggi-bi-perbaiki-sistem-pemberian-kompensasiMuljani, N. (2002). Kompensasi sebagai Motivator untuk Meningkatkan KinerjaKaryawan. Surabaya: FAkultas Ekonomi Universitas Katolik Widya Mandala.Muljani, N. (2002). Kompensasi sebagai Motivator yang Meningkatkan Kerja Pegawai. Jurnal Management & Kewirausahaan, 4 (2), 108-122.Parthasarathy, A., Menon, K., & Bhattacherjee, D. (2006). Executive Compensation, Firm Performance and Corporate Governance : An Empirical Analysis. Economic and Political Weekly, 41, 4139-4147.Pinanda, D. (2018). Kinerja Guru : Kompentasi Guru, Motivasi Kerja dan Kepemimpinan Kepala Sekolah. Jawa Barat: CV Jejak.Putri, T., & Rahadian, Y. (2013). Pengaruh kinerja, Corporate Governance and Leverage terhadap Tingkat Kompensasi Dewan Direksi dan Komisaris. Fakultas Ekonomi Universitas Tanjungpura.Raharjo, E. (2007). Teori Agency Dan Teori Stewardship Dalam Perpektif Akuntansi. Fokus Ekonomi, 2 (1), 37-46.Raithatha, M., & Komera, S. (2016). Excutive Compensation and Firm Peformance :Evidence from Indian Firms. IIMB Management Review, 28, 160-169.Republik Indonesia. (2016). peraturan Otoritas Jasa Keuangan (OJK) No 45 /POJK.03/2015 Tentang Penerapan Tata Kelola Dalam Pemberian Remunerasi Bagi Bank Umum.Sari, S. P., & Harto, P. (2014). Kompensasi Eksekutif dan Kinerja Operasional Perbankan Indonesia. Diponegoro Journal of Accounting, 3 (2), 1-7.Scott, W. (2012). Fianancial Accounting Theory (6 ed.). Toronto: Pearson Education Canada.Singgih, S. (2012). Aplikasi SPSS Pada Statistik Parametrik. Jakarta: PT. Excel Media Komputindo.Subagyo, J. (2011). Metodologi Penelitian Dalam Teori Dan Praktek. Jakarta: Aneka Cipta.Subramanyam, & Wild, J. (2010). Analisis Laporan Keuangan . Jakarta: Salemba Empat.Sugiyono. (2006). Metode Penelitian Bisnis. Bandung: CV ALFA.Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung: Afabeta.Sugiyono. (2012). Statistika untuk Penelitian. Bandung: Alfabeta.Sugiyono. (2014). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Afabeta.Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Afabeta.Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Afabeta.Suherman, Fitriawan , R., & Ahmad, G. N. (2015). Pengaruh Kinerja Perusahaan, Kepemilikan Institusi, dan Komisaris Independen terhadap Total Kompensasi: Studi pada Perusahaan yang Terdaftar di LQ45 Tahun 2009â€“2012. Jurnal Aplikasi Manajemen (JAM), 13 (3), 516 - 526.Suherman, Pardede, Y. Y., & Mardayati, U. (2016). Pengaruh Kinerja Perusahaanm Corporate Governance and Karakteristik Eksekutif terhadap Kompensasi Eksekutif. Jurnal Keuangan dan Perbankan, 20 (1), 1-9.Universitas Tanjungpura, F. (2017). Pedoman Penulisan Karya Akhir.Vidyatmoko, D., Sanim, B., Siregar, H., & Didu, M. (2009). Analisis faktor Penentu Kompensasi Dan Hubungan Kompensasi Dengan Kinerja Perusahaan. Jurnal Sains dan Teknologi Indonesia, 11 (3), 181-187.Yundiarto, Y. (2015, September 9). SWA Business Research. Dipetik November 7, 2019, dari SWA: https://swa.co.id/swa/trends/business-research/survei-gaji-2015-perbankan-paling-tinggi-gajinya